Kant and the French Revolution - Maliks, Reidar; Menéndez Menéndez, Trad., Agustín José (Las Torres de Lucca. International Journal of Political Philosophy, 2023)
Like the French revolutionaries, Kant defended individual rights and a republican constitution. That he nonetheless rejected a right of revolution has puzzled scholars. In this article I give an overview of Kant’s rejection of a right of revolution, compare it to the German intellectual context, and use it to explain Kant’s view of the events in France. In Kant’s nuanced account of the revolution’s two central phases, he refined a distinction between legitimate political transition and lawless popular rebellion.